Perhitungan Debit Uap Boiler dan Ketercapaian Kebutuhan Uap Pabrik Kapasitas 45 Ton/Jam - Bekti Santoso; Ahdiat Leksi Siregar; Indriana Lestari (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
A Boiler is an energy conversion machine that converts water to steam, which occurs due to continuous heating. The steam produced can be used for all equipment that requires steam at a palm oil mill (POM), especially power turbines. In addition, other equipment are sterilizers, pressing station, kernel recovery station and clarification station. The quality and quantity of steam produced must be based on their need, because if it is not achieved it will disrupt the processing in the POM. This study purpose to calculate the quantity of steam needed for palm oil processing in POM. This research was conducted on May 7th until May 12th, 2018. This study used a descriptive method with data gathering techniques by observation, documentation and interview. The result showed that the average steam discharge was 30,523 Kg/hour, while the steam requirement for turbine operation with an actual power of 1,200 Kw was 26,400 Kg and for the palm oil processing was 24,750 Kg/hour. Steam discharge generated by the boiler is over than the mill capacity of 45 Tons/hour, so that the steam discharge generated by the boiler is sufficient to meet the steam need in the POM.